Sequência didática para o ensino de ciências no ensino fundamental II: contribuições teórico-práticas para educação ambiental na caatinga - Santana, Daiane Moura de (2020)
The perception of the caatinga environment by students in the region has been the subject of discussion in several studies that indicate that students do not recognize it and do not recognize themselves as inhabitants of this biome. This issue was also confirmed from the author's experience. Thus, this research seeks to systematize new strategies for teaching science to semi-arid children. From a qualitative participatory research, which is structured through a didactic sequence as a pedagogical intervention strategy. It was held with students in the final grades of elementary school, in a rural school in the municipality of Ipecaetá, Ba. Having as central objective to understand the potential of using didactic sequence for science teaching in Elementary School II in a rural school and its theoretical-practical contributions to environmental education in the caatinga. And specific: Diagnose students' previous knowledge about the caatinga biome, considering their daily knowledge; Identify and experience elements of the caatinga landscape that characterize it as a biome of multiple plant, animal and cultural riches; Promote learning situations that enable the construction of knowledge and the valorization and preservation of the caatinga biome; Evaluate the insights acquired in the process of building new ones; students' knowledge of the caatinga biome considering the physical aspects and biological diversity and; Disseminate research results to the school and scientific community through lectures and production of scientific articles. The importance of scientific knowledge, Scientific Literacy (LC), Rural Education, Ecopedagogy in the Caatinga and Didactic Sequence as a Strategy for the Redefinition of Science Teaching were approached. Methodologically, the needs of students were raised through pre-testing and listening. Then, an intervening plan was drawn up with field trips, mental maps of the trail carried out in the community, cultural exhibitions and films and post-tests to evaluate the results. The group of students who took part in this intervention was composed of fourteen members, in the pre-text 28.5% stated that all the caatinga environment is extremely dry, unhealthy and poor. After the intervention, only 14% perceived difficulties in planting in the dry season, but they already recognized the peculiarities and riches of the caatinga, 64% of the students presented positive positions about the caatinga. Thus, it is concluded that the strategy, didactic sequence, proved to be quite efficient for the scientific and environmental education work carried out, contributing to the reduction of distorted and negative ideas of the caatinga and the reduction of a stigmatized vision about the biome. Distorted associations are directly linked to the low access to quality information and cultural influences in these historically neglected regions. This requires new directions and new meanings for the contents and methodologies applied in the classroom, which builds knowledge based on the protagonists of the students.